Mefenamic acid-induced bullous pemphigoid. Issue 723 (January 1986) - Shepherd, A. N.; Ferguson, J.; Bewick, M.; Bouchier, I. A.
Abstract : A 52 year old man developed bullous pemphigoid, Coombs' positive haemolytic anaemia and diarrhoea related to the use of mefenamic acid. Clinical manifestation of the bullous pemphigoid, haemolytic anaemia and diarrhoea resolved following discontinuation of the mefenamic acid. Mefenamic acid should be added to the list of agents that are known to induce bullous pemphigoid.